The cultural history of Shanran al-Aridah tribe from the Umayyad era to the third Saudi Kingdom / Ali Saad Al Zahifah Al-Shahrani - Ali , Saad Al Zahifah Al Shahrani (2016)
Answering the call to re-write the Social History of the Kingdom of Saudi based on new, reformed perspectives of recent years and with the purpose to extend and overcome writings on the topics of political history with an orientation towards highlighting social, economic and cultural aspects following the point of view highlighting effective roles of society in historical events witnessed in the Kingdom of Saudi Arabia. On this basis, this study will be giving importance and focusing on the cultural roles for Syahran Al-‘Aridhah Tribes which are considered the most reknowned of Arabic tribes that plays important cultural, political and economic roles in the history of the Kingdom of Saudi Arabia. Although the roles played were amongst the most important roles played, there is still no study and analysis done on them. Therefore, this study intends to try to identify and analise these important roles and the different patterns in their cultural, scientific and literature heritage between the time of the Umayyad Caliphate until the formation of the third Arab State. As an added point, contributions of these tribes throughout the priod studied in the dissemination of knowledge will be also be included. Historical analysis and descriptive method will be used in this study, together with interviews conducted with a number of Syeikhs of the Tribes, their most reknowned narrators and historians. This research was able to gain some important findings throughout this study, amongst them being that the Syahran Tribes possess a wide social heritage, that include their scholars’ and writers’ roles in enriching their cultural and intellectual life. Thus, this study suggests the need to preserve these social heritage of the said tribe together with the other tribes by arranging and directing scientific studies around its studies, its analysis and its documentation. By doing so, a connection and analysis of those phenomenon with their cultural, social and scientific patterns that contributes greatly in the understanding of today’s social reality in order to solve the many problems and barriers faced by the society. Then, returning to history and extracting their contributions on the societal level will lead to the revelation of the most important historical events.